La Liofilizzazione come Metodo per il Salvataggio di Beni Cartacei - Pittino, Hellen (Archeomatica, 2016)
Ever more frequently we hear about material archives being lost and destroyed by damages caused directly and indirectly by water. Salvaging a cultural heritage of documents damaged by flooding is a job that can be done, thanks to the advanced technologies, which have been created over the years by the combined knowledge of expert restorers, biologists and engineers, and which are now being employed worldwide by industries and organizations interested in the field of the preservation of cultural heritages. One of the methods used to obtain the best results for regenerating the damaged materials, to enable them to still be useful for many more years to come, is that of the vacuum freeze-drying process which does not use potentially harmful chemicals for humans or for the material to be retrieved.